Suspended Sediment Dynamics in the Macrotidal Seine Estuary (France): 1. Numerical Modeling of Turbidity Maximum Dynamics. Issue 1 (24th January 2018) - Grasso, F.; Verney, R.; Le Hir, P.; Thouvenin, B.; Schulz, E.; Kervella, Y.; Khojasteh Pour Fard, I.; Lemoine, J.‐P.; Dumas, F.; Garnier, V.
Abstract: Tidal pumping, baroclinic circulation, and vertical mixing are known to be the main mechanisms responsible for the estuarine turbidity maximum (ETM) formation. However, the influence of hydro‐meteorological conditions on ETM dynamics is still not properly grasped and requires further investigation to be quantified. Based on a realistic three‐dimensional numerical model of the macrotidal Seine Estuary (France) that accounts for mud and sand transport processes, the objective of this study is to quantify the influence of the main forcing (river flow, tides, and waves) on the ETM location and mass changes. As expected, the ETM location is strongly modulated by semidiurnal tidal cycles and fortnightly time scales with a high sensitivity to river flow variations. The ETM mass is clearly driven by the tidal range, characteristic of the tidal pumping mechanism. However, it is not significantly affected by the river flow. Energetic wave conditions substantially influence the ETM mass by contributing up to 44% of the maximum mass observed during spring tides and by increasing the mass by a factor of 3 during mean tides compared to calm wave conditions. This means that neglecting wave forcing can result in significantly underestimating the ETM mass in estuarine environments. In addition, neap‐to‐spring phasing has a strong influence on ETM location and mass through a hysteresis response associated with the delay for tidal pumping and stratification to fully develop. Finally, simulations show that the uppermost limit of the Seine ETM location did not change notably during the last 35 years; however, the seaward limit migrated few kilometers upstream. Key Points: A realistic 3‐D numerical model of mud‐sand dynamics has been developed to investigate turbidity maximum dynamics of a macrotidal estuary The ETM location is driven by river flow and tides; the ETM mass is driven by tides and influenced more by waves than by river flow The neap‐to‐spring phasing substantially influences the ETM location and mass through a hysteresis response related to stratification, mixing, and tidal pumping mechanisms